2015
DOI: 10.1371/journal.pone.0122539
|View full text |Cite|
|
Sign up to set email alerts
|

Soil Bacterial Community Structure Responses to Precipitation Reduction and Forest Management in Forest Ecosystems across Germany

Abstract: Soil microbial communities play an important role in forest ecosystem functioning, but how climate change will affect the community composition and consequently bacterial functions is poorly understood. We assessed the effects of reduced precipitation with the aim of simulating realistic future drought conditions for one growing season on the bacterial community and its relation to soil properties and forest management. We manipulated precipitation in beech and conifer forest plots managed at different levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 76 publications
4
41
2
4
Order By: Relevance
“…We aimed to test if such a relationship could also be observed for the understory of beech dominated forests and conifer replacement stands. We found that understory Shannon diversity was, in fact, lower in the unmanaged beech stands compared to the other two management intensities and significantly higher at the Schwäbische Alb exploratory compared to the other two exploratories (Felsmann et al 2015). Plotting Shannon diversity against the impact of the drought treatment on community transpiration or community Δ 13 C, however, showed that understory diversity had no influence on the strength of the responses to drought (see Fig.…”
Section: 3mentioning
confidence: 73%
See 3 more Smart Citations
“…We aimed to test if such a relationship could also be observed for the understory of beech dominated forests and conifer replacement stands. We found that understory Shannon diversity was, in fact, lower in the unmanaged beech stands compared to the other two management intensities and significantly higher at the Schwäbische Alb exploratory compared to the other two exploratories (Felsmann et al 2015). Plotting Shannon diversity against the impact of the drought treatment on community transpiration or community Δ 13 C, however, showed that understory diversity had no influence on the strength of the responses to drought (see Fig.…”
Section: 3mentioning
confidence: 73%
“…The study was carried out at the three regions of the Biodiversity Exploratories (http://www.biodiversityexploratories.de; for details, see Fischer et al 2010): Schorfheide-Chorin (S) in the north-east, Hainich Dün (H) in the middle, and Schwäbische Alb (A) in the south-west of Germany as described recently by Felsmann et al (2015). In each of the Exploratories, we selected three forest stands, which represent different forest types, management intensities and comprise different vegetation communities (see table 1 in Gimbel et al 2015), but are similar with respect to topography and soil type within each exploratory (Table 1).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the abovementioned studies, the drought intensity in our study was rather moderate as we aimed to simulate the conditions in the forest understorey where extreme environmental amplitudes are buffered by the sheltering canopy (Hommel et al 2014;Felsmann et al 2015;Gimbel et al 2015), and thus we kept soil moisture tension close to but above the root water uptake thresholds.…”
Section: The Effect Of Moderate Drought On Allocation Of New Assimilamentioning
confidence: 99%